The role of local councils and administrative bodies of decentralization in spatial planning and the obstacles in Irbid Governorate / Jordan year 2021 - Al-Koury, Haitham Ahmad (Journal of Humanities & Social Sciences, 2022)
The study evaluated with the role of the decentralized local administration and councils in spatial planning in the governorate of Irbid, and the detection of the obstacles they face. The study concentrated on level of success in applying the decentralization in spatial planning in the study area through selective sampling from Irbid governorate. The descriptive analytical method was used to identify the level of decentralization implementation in Irbid governorate. The results showed that decentralization was not fully implemented in spatial planning due to many reasons included (1) lack of needed laws and legislation that make it run at the required level, (2) the presence of centralization in planning and decision making that make the role of these bodies at lower level, (3) they do not have the powers that enable them to work properly, (4) the absence of a competent planning apparatus, plans and legislation regulating spatial planning, (5) in addition to the weak public participation in the planning process and decision making. Based on the foregoing results, the study recommended necessary to develop the laws and legislations that control and define the functioning of decentralization and granting local bodies and council’s powers commensurate with its objective and giving them the ability to work. Public participation in the planning and decision-making process regarding the submitted projects, and the existence of a mechanism that works on integration and coordination between the ministries and agencies concerned with spatial planning.